Results Reporting and Early Termination of Childhood Obesity Trials Registered on ClinicalTrials.gov - Xinyi Wang; Xinyi Wang; Youlin Long; Youlin Long; Liu Yang; Liu Yang; Jin Huang; Jin Huang; Liang Du; Liang Du; Liang Du (Frontiers Media S.A., 2022)
ObjectiveChildhood obesity is one of the most severe challenges of public health in the twenty-first century and may increase the risk of various physical and psychological diseases in adulthood. The prevalence and predictors of unreported results and premature termination in pediatric obesity research are not clear. We aimed to characterize childhood obesity trials registered on ClinicalTrials.gov and identify features associated with early termination and lack of results reporting.MethodsRecords were downloaded and screened for all childhood obesity trials from the inception of ClinicalTrials.gov to July 29, 2021. We performed descriptive analyses of characteristics, Cox regression for early termination, and logistic regression for lack of results reporting.ResultsWe identified 1,312 trials registered at ClinicalTrials.gov. Among clinicalTrials.gov registered childhood obesity-related intervention trials, trial unreported results were 88.5 and 4.3% of trials were prematurely terminated. Additionally, the factors that reduced the risk of unreported outcomes were US-registered clinical studies and drug intervention trials. Factors associated with a reduced risk of early termination are National Institutes of Health (NIH) or other federal agency funding and large trials.ConclusionThe problem of unreported results in clinical trials of childhood obesity is serious. Therefore, timely bulletin of the results and reasons for termination remain urgent aims for childhood obesity trials.